Efektivitas Model Pembelajaran Interaktif dalam Pendidikan Agama Kristen untuk Anak-anak - Sukma Mulyani; Retno Nurasisyah; Yasinta Fitria Sawalina (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This study tested the effectiveness of an interactive learning model in improving children's understanding of biblical values. With a quasiexperimental design, the study involved 120 elementary school students in three churches. The results showed that interactive approaches, such as roleplaying and group discussions, improved students' retention and engagement. This study suggests the application of an experiential learning model for Christian religious education.